PENGARUH AIR BERSIH DAN STATUS EKONOMI TERHADAP KEJADIAN STUNTING DI WILAYAH KERJA PUSKESMAS TAPUNG HILIR II - Riski Novera Yenita; Masyitha Ramadhani; Evy Saputri (EcoNews, 2021)
Infant and toddler mortality rates due to diseases that can be prevented by immunization still show quite high rates. Basic immunization serves to protect and reduce the risk of morbidity and mortality from diseases that can be prevented by immunization. The purpose of this study was to determine the factors that influence mothers in providing routine routine immunizations in the work area of ​​Inuman Health Center. This type of research is observational analytic with the "cross sectional" approach. The population in this study is mothers who have under two years (under two years) with a sample of 176 people with a sampling technique is purposive sampling. Data were analyzed by Univariate and Bivariate with Chi Square Test. Statistical test results found that there is a significant relationship between knowledge factors (p value: 0,000 <α 0.05), education (p value: 0.018 <α 0.05), employment (p value: 0,000 <α 0.05), attitude (p value: 0,000 <α 0.05), income (p value: 0,000 <α 0.05), family support (p value: 0,000 <α 0.05) and affordability to the posyandu service center (p value: 0,000 < α 0.05) towards the provision of complete routine immunizations in the Inuman Community Health Center Work Area. It is recommended that the results of this study be considered by Inuman Health Center to conduct health promotion in the form of education about the importance of immunization for mothers who have babies and their families.